Polishing inner wall of crossed deep micropores using magnetic microabrasive jet technology - Zezhi WANG; Jie WANG; Xiaogang MA; Fan LI; Xinya FAN; Yan CHEN (Jin'gangshi yu moliao moju gongcheng)
ObjectivesPrecision micro through-hole parts are widely used. However, due to the limitations of manufacturing technology, precision parts with complex shapes, such as cross micro-holes, may have defects such as burrs, scratches, and nodules during the manufacturing process. In view of the problems of conventional finishing processing of cross deep micro-holes being limited by size, uneven processing, and poor quality, and combined with the characteristics of a stable removal function and strong adaptability of the abrasive jet, the magnetic micro-abrasive jet technology finishing processing method is proposed to improve the quality of the inner wall of cross deep micro-holes.MethodsAn independent magnetic abrasive jet device was used to carry out finishing tests on the cross deep micro-holes, and an electromagnetic device was used to generate a focusing magnetic force near the nozzle outlet. The magnetic abrasive was concentrated towards the center during the internal movement of the nozzle, alleviating the problem of rapid divergence of the magnetic abrasives with the jet after spraying and further improving the efficiency of finishing processing. A simulation mathematical model was established to explore the influence of different process parameters on the finishing effect. The finite element method and the discrete element method were coupled to simulate the polishing process of the inner wall of deep micro-holes by the magnetic micro-abrasive jet under different process parameters. The flow field distribution, the erosion rate, and the action law of wall shear force under different parameters were analyzed, and the key factors were identified. Finally, the response surface method was used to optimize the three factors of jet target distance, jet pressure, and nozzle diameter. The response surface equation was established and solved by taking the comprehensive influences of wall shear force and erosion rate on the orifice, the inner wall of the hole, and the cross part of the hole as the response value, and the optimal combination of process parameters was obtained and verified by the test.ResultsAdding a focusing magnetic field near the nozzle can effectively reduce the divergence of the abrasive after jet ejection, and further improve the efficiency and quality of magnetic abrasive ejection polishing of cross deep micro-holes. The simulation results show that the main parameters affecting micro-hole finishing are jet target distance, jet pressure, and nozzle diameter. By using the response surface method combined with experiments for parameter optimization, the optimal process parameter combination for magnetic micro-abrasive jet finishing of cross deep micro-hole inner walls is obtained, which includes a jet target distance of 7 mm, a jet pressure of 1.0 MPa, and a nozzle diameter of 1.4 mm. Under the optimal combination of process parameters, the inner wall quality of the cross deep micro-holes is significantly improved, the burrs at the cross-holes are completely removed, the wall roughness Ra is reduced from 0.49 μm to 0.13 μm, and the orifice has a good rounding effect.ConclusionsBy combining magnetic fields and abrasive jets, the magnetic micro-abrasive jet technology provides a new method for the finishing of cross deep micro-holes. Due to the ability of the magnetic abrasive micro-jet to achieve focused fixed-point machining, it has significant processing advantages in cross deep micro-hole finishing and deburring. By constructing a physical model of the machining process and using the simulation form of coupling the finite element method and the discrete element method, it is possible to more clearly simulate the motion of the abrasive and flow field in the abrasive water jet during the machining process, as well as the force situation of the workpiece being machined. In the finishing process of cross-hole parts, the nozzle diameter, pressure, and target distance have a direct impact on the finishing effect. However, parameter adjustment is required for finishing workpieces of different sizes and shapes. Finding suitable processing parameters will further improve the quality and efficiency of workpiece processing.